A Simple and Rapid Estimation of Totals Polyphenols Based On Carbon Paste Electrode Modified with Ruthenium Oxo-Complex - Raymundo-Pereira, Paulo A. [UNESP]; Teixeira, Marcos F. S. [UNESP]; Caetano, Fábio R.; Bergamini, Márcio F.; Marcolino-Júnior, Luiz H. (Wiley, 2015)
A simple and fast method based on electrochemical measurements was proposed for estimation of total polyphenols using a carbon paste modified electrode. The method was based on catalytic response exhibited by a ruthenium complex [(bpy)2(NH3)RuIII(μ-O)RuIII(NH3)(bpy)2]4+ in presence of gallic acid (GA). Calibration plots using chronoamperometry (CA) showed a linear response for GA concentrations ranging from 6.6×10-6 to 1.9×10-4molL-1 with a detection limit of 4.9×10-7molL-1. Comparative studies using the official method revealed a good agreement between methods suggesting that the proposed method can be applied for polyphenol estimation without any sample treatment.
Keywords: Carbon paste modified electrode; Gallic acid; Polyphenols estimation; Ruthenium oxo-complex